2022
DOI: 10.2147/idr.s340866
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Associated Risk Factors of Ovine Brucellosis in South Omo Zone, Southern Ethiopia

Abstract: Background Brucellosis is a zoonotic disease with economic and public health significance in developing countries that rely on livestock production including Ethiopia. This study intended to establish the seroprevalence and associated risk factors of ovine brucellosis. Methods A cross-sectional study was carried out on seroepidemiology of ovine brucellosis from January 2017 to June 2020 G.C in five districts of South Omo zone, Southern Ethiopia. A total of 1536 sera sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…In the current study, greater FS (> 50 heads) of small ruminants was shown to be significantly associated with brucellosis by both univariate and multivariate analyses. Previously, Gompo et al [ 27 ] and Sorsa et al [ 28 ] also reported similar findings. This association can be attributed to increased transmission opportunities in more extensive flocks due to the closer proximity of animals.…”
Section: Discussionsupporting
confidence: 70%
“…In the current study, greater FS (> 50 heads) of small ruminants was shown to be significantly associated with brucellosis by both univariate and multivariate analyses. Previously, Gompo et al [ 27 ] and Sorsa et al [ 28 ] also reported similar findings. This association can be attributed to increased transmission opportunities in more extensive flocks due to the closer proximity of animals.…”
Section: Discussionsupporting
confidence: 70%
“…Regarding the history of infertility as a risk factor for the three abortive diseases, our result showed that ocks with problems of infertility had 4.1 (OR = 4.1, 95% CI = 2.1-8.2) and 2.6 (OR = 2.6, 95% CI=1.4-4.7) times higher risk for infection with brucellosis and Q fever, respectively. This is not surprising since the ewes with reproductive problems were more exposed to abortion and an association with infertility and abortive diseases was reported (Martini et al 1994, Ullah et al 2020, Sorsa M et al 2022). Control of new introduction is signi cantly associated with the seroprevalence of brucellosis and farms practicing the introduction of animals without any test are 2.05 times more likely to be infected.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding the history of infertility as a risk factor for the three abortive diseases, our result showed that flocks with problems of infertility had 4.1 (OR = 4.1, 95% CI = 2.1–8.2) and 2.6 (OR = 2.6, 95% CI = 1.4–4.7) times higher risk for infection with brucellosis and Q fever, respectively. This is not surprising since the ewes with reproductive problems were more exposed to abortion and an association with infertility and abortive diseases was reported (Martini et al [ 49 ], Ullah et al [ 50 ], Sorsa M et al [ 51 ]). Control of new introduction is significantly associated with the seroprevalence of brucellosis and farms practicing the introduction of animals without any test are 2.05 times more likely to be infected.…”
Section: Discussionmentioning
confidence: 96%